Synthesis and Characterization of Mn3O4 - Graphene Core - Shell Quantum Dots for Electrochemical Pseudocapacitor Applications - Ko, Yohan; Son, Dong Ick (KOREAN PHYSICAL SOC, 2018)
We report on the in-situ chemical growth of unique core-shell quantum dots (QDs) with single layer graphene on the surfaces of the Mn3O4 QDs and on their structural, optical and electrical properties. The Mn3O4-graphene QDs were synthesized through a simple hydrothermal technique. In order to enhance performance for electrochemical energy storage, we developed core (active material) - shell (conductive material)-type Mn3O4 - graphene QDs as electrode materials by using an aqueous electrolyte (6M KOH). As a result, the performance of electrochemical energy storage exhibit a specific capacitance of 452.72 Fg(-1) at a current density of 1 Ag-1.
Keywords: HYDROTHERMAL SYNTHESIS; SUPERCAPACITOR; OXIDE; FACILE; NANOCRYSTALS; PERFORMANCE; ELECTRODES